Study on the effectiveness of orientation class about rational prescription on interns - Thottol, Reema T.; M., Anuradha; M. V., Sajna (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Prescribing is one aspect of patient care where it is possible to do considerable harm if not done judiciously. The first experience of unsupervised prescribing begins during the internship year. Junior doctors are the most frequent prescribers in the hospital setting and are reported to make most of the prescribing errors. The Objective of the study was to study on the effectiveness of orientation class about rational prescription on interns. Methods: Sample size was 100 students attending orientation course at the beginning of intern ship. This study was done in Government Medical College Kozhikode, after getting ethics Committee approval. Total of 100 interns were included in the study. Pre-test was conducted to assess the prescribing skills by giving one case scenario, followed by a class on rational prescription writing. 14 questionnaires are made and prescription quality is assessed. Post-test was given after 2 weeks where the same previous case scenario repeated. Results: This study shows that orientation class about rational prescription during the beginning of internship improves the quality of prescription writing. Among the 14 parameters made for assessment of quality of prescription thirteen shows significant P value. So it is very effective to take orientation class about rational prescription during the internship period. Conclusions: It is very effective to take orientation class about rational prescription and periodic updating during the internship period improves the quality of prescription. As they learn the basics of prescription writing during their third semester only. Thus we can reduce the prescribing errors.